The Impact of Parental Health on Children's Schooling and Labour Force Participation: Evidence from Vietnam - Silvia Mendolia; Thi Nguyen; Oleg Yerokhin (Institute of Labor Economics (IZA), 2017)
This paper investigates the relationship between parental health shocks and children's engagement in education and labour market, using a panel data survey of Vietnamese families, interviewed between 2004 and 2008. While there is substantial evidence showing the intergenerational transmission of health, the literature investigating the impact of parental health on children's educational and labour market outcomes is limited, especially in developing countries. We use child fixed effects and control for a detailed set of household and local area characteristics. Our main findings show that maternal illness substantially decreases chances of being enrolled in school for children between 10 and 23 years old and, at the same time, increases the children's likelihood of entering the labour market and working more hours for children aged 10-15 years old. The effect is particularly pronounced for girls, who seem to experience worst adverse consequences in terms of education and labour market engagement.
Keywords: I10; I14; I24; 330; children's education; child labour; parental illness